Teeth Samples in Forensic Evidence: A Literature Review - Taif Mothhar Al-Khalidi (Journal of Global Pharma Technology, 2017)
Dental identification seem to be more powerful source in forensic evidence to identification disaster victim, mass graves and fires victims .DNA evidence can eliminate suspect so it consider as tool for innocence or condemnation. Use dental record as x-ray and dental cast can allow dental remains to be connected to victim. In brief, pulp and cement um are most appreciated sources of nuclear DNA in the tooth and both these tissues and dentine are good sources of mt DNA. Dentine and pulp are protected via enamel. Teeth are not in save from contamination their lower porosity make them most resistant to contaminants than skeleton (bone).This research present a literature review refer to importance of forensic dentistry and the main methods of extraction DNA from teeth samples and the role of DNA in teeth in forensic investigations.Keywords: DNA, PCR Inhibitors, Forensic Destiny, Human identification.